Professional Activity of a University Teacher: Personal Values and Temporal Perception - N. B. Moskvina; B. E. Fishman (Высшее образование в России)
The purpose of the article is to actualize the problems of personality values and senses in university teachers’ professional activities. The authors present and substantiate the methodology for identifying the relation between personal significance for teachers of various aspects of their professional activities and time costs for the implementation of these aspects (components). The methodology is based on their pairwise comparison. This comparison is carried out first by the criterion of the significance of these aspects, and after 1-2 weeks – by the criterion of their time cost. Based on their own work as well as other studies, the authors identify three of the most timeconsuming aspects of teachers’ activity: the preparation and conducting of lessons and lectures; scientific products creation; work with documents. It is confirmed that the preparation and conducting of lessons and lectures as well as the preparation of various plans, programs, reports, etc. are the dominant components of university teachers’ activity. The disparity between the personal significance and time costs is the smallest if it concerns preparation of lessons. In this case, the time cost is compensated by understanding of its importance. As for work with documents, such compensation does not exist here. So, it turns into a potential source of internal tensions and conflicts. The component “creation of scientific products” is quite contradictory: time costs for it subjectively seem quite large while this component is perceived as not high significant. This is consistent with other studies that show that this aspect of activity often turns out to be formally motivated, not related to serious scientific research. In the article, the situation, empirically recognized by many authors, gets a fundamentally new interpretation, as the temporal parameter acquires the status of value. The authors propose to consider time costs in relation to various aspects of university teachers’ activities in this particular context.